Learning with multiple online texts as part of scientific inquiry in the classroom. (January 2019) - Sullivan, Sarah; Puntambekar, Sadhana
Abstract: The aim of this study was to investigate how teachers interact with students in order to prepare them to conduct research with multiple online texts as part of the process of scientific inquiry in the classroom. The specific focus of this work was on understanding how teachers used classroom dialogue to create an environment that supports the use of multiple online text-based resources as part of the process of doing science. Data collection for this study occurred in the 6th grade classrooms of two teachers in a Midwestern school district. Each of the teachers taught three science classes for a total of 150 students. A test of students' content knowledge of physics was used in order to evaluate students' understanding of the physics concepts targeted in the curriculum. An analysis of covariance (ANCOVA) revealed that the students from one teacher's classes performed significantly better on the physics test than the students of the other teacher (p < .05). To qualitatively investigate the differences between the whole class dialogue used by the two teachers, teachers' interactions with students as they prepared them to engage in research with the multiple texts were coded. Coding of the dialogue revealed that the teacher whose students exhibited higher learning outcomes engaged in more deep level facilitation strategies during whole class discussion, including setting learning goals for text interactions, connecting to prior knowledge, and discussing the use of multiple texts as part of doing science. Highlights: Teachers differed in their facilitation strategies but not in discourse structure. Deep level facilitation strategies were associated with better learning outcomes. Setting learning goals for text interactions seemed to impact knowledge development. Stressing personal and conceptual relevance helped students to connect with texts. Discussing use of multiple texts as part of science was a key facilitation strategy.